Adoption and impact of gaps in pig value chains: Implications for institutional policy and practice change - Lapar, Ma. Lucila; Nguyen Thi Duong Nga; Nguyen Thi Thinh; Nguyen Thi Thu Huyen; Unger, Fred; Grace, Delia (Kasetsart University, 2017)
This paper investigates the adoption of VietGAHP, a set of guidelines for best practices in pig production, and evaluates impacts using quantitative and qualitative indicators. It tackles the following specific research questions: 1) What is the extent of adoption of VietGAHP among smallholder pig producers? 2) Is there a difference in performance between VietGAHP adopters and non-adopters? Outcomes from adoption and compliance with VietGAHP are assessed using reduction in mortality as a metric for efficacy. Cost-benefit comparisons are also made to illustrate economic outcomes as a measure of effectiveness. We employ statistical t-tests for mean comparison of outcomes between VietGAHP adopters and non-adopters and across exposed and control sites. Our study shows productivity gains from practice and behavioral changes elicited from adoption and compliance with VietGAHP outweigh the costs of doing so, at least at the household level. The observed economic and market incentives could boost the adoption of VietGAHP if these incentives are sustained with appropriate institutions in place. Scalability could be facilitated by exposure via demonstration effects. Peer-to-peer learning is an effective strategy in enhancing capacity for uptake. With exposure being strongly linked to uptake, regardless of gender of respondents, training opportunities for non-exposed groups are worthwhile to pursue.